The Euro is good after all: Evidence from corporate valuations - Arturo Bris; Yrjö Koskinen; Mattias Nilsson (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
In this paper we study the changes in corporate valuations induced by the adoption of the euro as the common currency in Europe. We use corporate-evel data from ten countries that adopted the euro, the three EU countries that did not start using the euro, as well as Norway and Switzerland. We show that the introduction of the euro has increased Tobin's Q-ratios by 16.7% in the euro-countries that previously had weak currencies. The increase in Q-ratios decreases to 8.7% once we take into account the changes in the interest rates. The increases in Tobin's Q are larger for firms that were exposed to intra-European currency risks, i.e. firms that were ex-ante expected to benefit more from the common currency. Finally, the increases are also more significant for financially unconstrained firms. The evidence supports the view that the introduction of the euro has lowered firms' cost of capital in the euro-countries.
Keywords: F33; F36; G32; 330; Economic and Monetary Union (EMU); the euro; valuation; cost of capital; currency risk; currency union; Europäische Wirtschafts- und Währungsunion; Investition; Kapitalkosten; Schulden; Wechselkursrisiko; Euro; EU-Staaten